Islamic finance and investment in the halal industry: A systematic literature review - Wahyudi, Tri; Bin Bakar, Mohd Hafiz; Soleha, Nurhayati (International Journal of Halal Industry, 2026)
Purpose – This study aims to examine the role of Islamic finance and investment in supporting the halal industry’s development by synthesizing existing academic literature on financing instruments, economic impacts, and ecosystem development pathways. Methodology – A systematic literature review (SLR) was conducted using structured search strategies and selection procedures. Relevant studies were identified from major academic databases and screened using defined inclusion and exclusion criteria. The selected literature was analyzed thematically to identify patterns in Islamic financial instruments, economic outcomes, governance mechanisms and ecosystem development within the halal industry. Findings – The review reveals that Islamic finance contributes to halal industry development through multiple channels, including Shariah-compliant financing instruments, financial inclusion, regulatory governance, and innovation in fintech. Instruments such as Islamic banking, Sukuk, crowdfunding, and fintech platforms support halal business expansion by improving access to capital and strengthening the halal value chain. Implications – The findings suggest that policymakers, financial institutions, and halal industry stakeholders should strengthen institutional coordination, improve financial literacy, and develop integrated halal ecosystem frameworks that link financing mechanisms with certification, governance, and market development to promote halal SMEs. Originality – This study provides a comprehensive synthesis of the fragmented literature on Islamic finance and halal industry development by proposing an ecosystem-oriented perspective that integrates financing instruments, governance structures and halal value chain dynamics.